Il razzismo della prosperitÃ nell'Europa contemporanea - Riflessioni a margine del pensiero antirazzista di Walter Lorenz - Velleda Bolognari (Social Work and Society, 2007)
Recent publishing on the migration phenomena in the communitarian and globalized Europe, puts in evidence a fundamental racism which is capable of making cultural processes grow and feed both chaos and social disorder. As a matter of fact we are approaching the ending debates on multicultural citizenship as well as on solidary integration and antiracism. Since the appearing of these phenomena, namely the huge post colonial migration in the nineteen-eighties, by which the colonized countries became almost "emigrant nurseries", one could expect their stabilization. On the contrary, globalization and migration (twin subjects) everywhere still produce, at various levels, social disturbances together with some chauvinistic limitations as an ultimate kind of western prosperity defense. The peculiar European features of this new racism, less than ideological (superiority, homogeneity and civilizing mission), are confined to the concepts of patriotism, inequality and exclusion. In these terms one can understand why the new economic expansionism and the quest for new world markets makes European policies unstable, which remain undecided between conservatism, liberalism and extreme right. All this explains at least two things: the existing ambiguities of some European policies aiming to enhance particular forms of protectionism, and the difficulties in which the antiracist thought seems to be embedded. Indeed, according to what Walter Lorenz has already made clear, by using a well founded methodology, which prevents any fruitless protestations, it is impossible to contrast racism and nationalism. In such context, the educational field should try to use an operative epistemology. In other words the antiracist thought should dispose of competences and skills and, especially, personal and reflective capabilities. All this in order to avoid that which, in different historical scenes, permit the revival of the sense of moral opprobrium could not be identified with the political alibi to maintain privileges as well as advantages for the exclusive benefit of wealthy countries.